Influencing factors and variation laws of ventilation and heat dissipation characteristics of Φ15 m shield tunnel - Yimin Xia; Yongchao Zhou; Yazhou Zhang; Xuemeng Xiao; Zixiong Zhou (Alexandria Engineering Journal, 2025)
This study proposes a approach for enhancing and predicting ventilation and heat dissipation performance in large-diameter shield tunnels through Computational Fluid Dynamics (CFD). A comprehensive steady-state airflow model was developed to analyze heat-flow coupling in Φ15 m shield tunnels. The numerical model's reliability was rigorously validated through field measurements of velocity and temperature distributions at the construction site. Extensive steady-state CFD simulations were performed to systematically evaluate the average velocity and temperature variations under diverse ventilation conditions. The results reveal that implementing a double-duct air supply configuration in the shield ventilation system significantly improve flow uniformity, reducing the non-uniformity coefficient by 33.6 %. Optimal operational parameters are identified for Φ15 m shield tunnels: an air supply volume of 22–24 m³ /s, a duct outlet-to-shield tail distance of 10–12 m, and a duct diameter range of 1.0–1.2 m through systematic analysis. Furthermore, the study establish empirical correlations between key influencing factors and velocity/temperature distributions based on simulation data, providing a valuable tool for assessing ventilation performance and optimizing design parameters in shield tunnel engineering applications.